Perioperative Complications of Liver Resection in the Elderly with Hepatocellular Carcinoma: A Comparison with Younger Patients - Ruey-Horng Rau (International Journal of Gerontology, 2009)
Background: Liver resection surgery in patients with hepatocellular carcinoma is a high-risk procedure with an in-hospital mortality rate around 5%. Patient age and volume of blood loss were found to be independent predictive factors of long-term outcomes in previous studies. We sought to clarify the age-related differences in the perioperative complications during the whole admission for liver resection surgery. Methods: This retrospective study included 210 patients scheduled for elective liver resection from July 2006 to July 2008. The characteristics of the patients, intraoperative events, and postoperative complications were retrieved from medical charts, anesthesia records stored in a computer database, and the quality assurance system in our department. The patients were divided into two groups: Group A, aged 60 years or older (n = 91); and Group B, aged younger than 60 years (n = 119). Postoperative complications and intraoperative parameters were compared using the Student's t test for continuous data, and χ2 test for categorical data. Correlations of age with blood loss, operation time, urine output, length of intensive care unit stay, total admission time, and intubation time were examined with the Pearson's correlation. Analysis of variance was used to investigate the endotracheal intubation time with different postoperative pain control methods. Results: No differences in intraoperative blood loss, total operation time, urine output during surgery, in-hospital death, difficulty of operation, and incidence of massive blood loss and oliguria were found between the two groups. The length of intensive care unit stay and total admission time were significantly longer in the elderly group (p = 0.04 and 0.01, respectively). There was a higher incidence of postoperative respiratory complications in the elderly as revealed by a longer intubation time in Group A than in Group B (p = 0.03). Conclusion: In contrast to some surgeries for emergency conditions such as long bone fracture or acute abdomen, the perioperative complications in the elderly receiving elective liver resection surgery did not differ markedly from those of younger patients. However, elderly patients would benefit even more if comprehensive postoperative care or newly improved therapies can be provided to lessen the incidence of perioperative respiratory complications.